Developmental and Reproductive Outcomes in Male Rats Exposed to Triclosan: Two-Generation Study - Montagnini, Bruno Garcia; Forcato, Simone; Pernoncine, Karine Vandressa; Monteiro, Mariana Cunha; Pereira, Marina Rangel Ferro; Costa, Nathalia Orlandini; Moreira, Estefânia Gastadello; Anselmo-Franci, Janete Aparecida; Gerardin, Daniela Cristina Ceccatto (Frontiers in Endocrinology, 2021)
Triclosan (TCS) is a phenolic compound with broad-spectrum antimicrobial action that has been incorporated into a variety of personal care products and other industry segments such as toys, textiles, and plastics. Due to its widespread use, TCS and its derivatives have been detected in several environmental compartments, with potential bioaccumulation and persistence. Indeed, some studies have demonstrated that TCS may act as a potential endocrine disruptor for the reproductive system. In the current study, we are reporting on the results obtained for male rats after a two-generation reproduction toxicity study conducted with TCS. Female and male Wistar rats were treated daily by gavage with TCS at doses of 0.8, 2.4, and 8.0 mg/kg/day or corn oil (control group) over 10 weeks (F0) and over 14 weeks (F1) before mating and then throughout mating, until weaning F2 generations respectively. TCS exposure decreased sperm viability and motility of F1 rats at the dose of 2.4 mg/kg. The effects of TCS on sperm quality may be related to the exposure window, which includes the programming of reproductive cells that occurs during fetal/neonatal development.